Determinants of online dating Apps adoption intention among young adults in Malaysia - Chan, Xin Yi; Choy, Jey Ni; Chua, Zhen Ling; Ng, Sin Jie; Ong, Sook Kwan (2022)
The pandemic has posed new challenges and altered how most people date and hook up. The Unified Theory of Acceptance and Use of Technology (UTAUT) was applied in this research to discover determinants of online dating apps’ adoption intention among young adults in Malaysia. For this purpose, possible determinants that might affect the intention to adopt online dating apps are sought and critically reviewed. With reference to the model, the variables proposed in this research include performance expectancy, effort expectancy, social influence, facilitating conditions, and an additional variable – trust. Five hypotheses were constructed to identify whether the determinants will affect the Malaysian young adult’s adoption intention towards online dating apps. Questionnaires were distributed to young adults to obtain valid primary data from respondents. One of the limitations found in this research is the approach to collecting data causing the participants to overlook the questionnaires. Besides, restrictions were found in the demographic profile of the respondents. The study might not accurately reflect Malay and Indian individuals’ adoption intentions. The responses collected determine the adoption intention of young adults towards online dating apps within Malaysia only. This research contributes to the debate among online dating apps developers.